Phytoremediation as a Sustainable Solution for Mercury Contamination in Artisanal Gold Mining Sites: Insights from ASGM in South Lampung, Indonesia - Danasla, Muhammad Akbari; Anjelita, Chyndy; Julyanto, Rizqi Arbi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Artisanal and small-scale gold mining (ASGM) contributes significantly to mercury contamination, posing severe environmental and health risks due to the improper disposal and release of mercury into soil and water. This study investigated the potential of phytoremediation as a sustainable solution for mitigating mercury contamination at an ASGM site in XYZ Village, Katibung Subdistrict, South Lampung Regency, Indonesia.  Water and soil samples were collected from the field, and the study was conducted on a laboratory scale. Initial assessments revealed mercury concentrations of 0.367 mg/L in water and 74.8215 mg/kg in soil, both exceeding national regulatory limits. Phytoremediation trials were conducted using Eichhornia crassipes (water hyacinth), Pistia stratiotes L. (water lettuce), and Cyperus rotundus (nutgrass) under controlled conditions. Water hyacinth demonstrated 100% mercury removal efficiency in water within nine days, whereas nutsedge reduced mercury levels in soil by 61.8% over 21 days. The combined treatment of water hyacinth and water lettuce further enhanced mercury removal in the water samples. The results highlight phytoremediation as an effective, low-cost, and eco-friendly strategy for the rehabilitation of mercury-contaminated environments. This can be implemented in other places with similar conditions. Future research should focus on optimizing phytoremediation techniques and integrating them into community-based environmental management.